Assessment the knowledge of mothers ‘toward home accident among children less than five years in Polytechnic University of Sulaimani - Qasem, Attallah O.; Abas, Layla A.; Hama Hussein, Burhan A.; Qadir, Muhammed S.; Salih, Faisal Abdula (Kurdistan Journal of Applied Research, 2017)
Children accidents are an essential source of death and wounds among children during the first of life. Annually, millions of children are constantly becoming handicap or blemished because of mishaps.Objective: To assess knowledge of children mothers toward home accidents in polytechnic University of Sulaimani. Methodology: A simple random sample of (110) respondents were selected.. The data collected and composed during the utilization of a created questionnaire, with two parts; the first part assessed the knowledge of children mothers with (20) yes or no questions and the second part includes the mothers' demographic attributes. A pilot study was carried out for the period of December 18th to 28th 2015 in order to conclude the questionnaire accuracy during the use of (Test – Retest). A panel of (8) experts was include in the determination of the questionnaire content validity Data were analyzed through the application of descriptive statistical data analysis approach (frequency and percentage), and inferential data analysis approach (Mean of Scores).).The results of the study revealed, the mean age of the mothers was (1.86) years, (58.2%) of them had completed secondary school, (88.2%) of mothers have more than five children, (89.1%) of mother’s were in moderate socio-economic status, (47.3%) of mothers have personal reading information,(58.2) of the child were male,(13.6%) of mothers have knowledge about safe housing condition held in Maternal and Child Health Centers.The conclusion of this study revealed that, inadequate children mothers’ knowledge regarding home accidents among children less than six years held in Maternal and Child Health Centers during the antenatal period. So the recommendation are suggested, reinforces the need for effective education program via mass media, for mothers.